Incommensurate antiferromagnetic order in the manifoldly-frustrated SrTb2O4 with transition temperature up to 4.28 K - Li, Hai-Feng; Zhang, Cong; Senyshyn, Anatoliy; Wildes, Andrew; Schmalzl, Karin; Schmidt, Wolfgang; Boehm, Martin; Ressouche, Eric; Hou, Binyang; Meuffels, Paul; Roth, Georg; Brückel, Thomas (Frontiers in Physics, 2014)
The Néel temperature of the new frustrated family of SrRE2O4 (RE = rare earth) compounds is yet limited to ~0.9 K, which more or less hampers a complete understanding of the relevant magnetic frustrations and spin interactions and an exploration of potential interesting properties. Here we report on a new frustrated member to the family, SrTb2O4 with a record TN = 4.28(2) K, and an experimental study of the magnetic interacting and frustrating mechanisms by polarized and unpolarized neutron scattering. The compound SrTb2O4 displays an incommensurate antiferromagnetic (AFM) order with a transverse wave vector Q0.5 KAFM = (0.5924(1), 0.0059(1), 0) albeit with partially-ordered moments, 1.92(6) μB at 0.5 K, stemming from only one of the two inequivalent Tb sites mainly by virtue of their different octahedral distortions. The localized moments are confined to the bc plane, 11.9(66)° away from the b axis probably by single-ion anisotropy. We reveal that this AFM order is dominated mainly by dipole-dipole interactions and disclose that the octahedral distortion, nearest-neighbour (NN) ferromagnetic (FM) arrangement, different next NN FM and AFM configurations, and in-plane anisotropic spin correlations are vital to the magnetic structure and associated multiple frustrations. The discovery of the thus far highest AFM transition temperature renders SrTb2O4 a new friendly frustrated platform in the family for studying the nature of magnetic interactions and frustrations and exploring potential macroscopic functionalities and new quantum states.